Factors influencing post abortion outcomes among high-risk patients in Zimbabwe - C Mudokwenuy-Rawdon; VJ Ehlers; MC Bezuidenhout (AOSIS, 2005)
Post abortion complications remain one of the major causes of mortality among women of child bearing age in Zimbabwe. Based on this problem, factors associated with mortalities due to abortion were investigated with the aim of improving post abortion outcomes for Zimbabwe's women, and possibly also for women of other African countries. Cases and controls were selected from 4895 post abortion records to conduct a retrospective case-control study. Significant risk factors identified for reducing mortalities due to post abortion complications included the administration of oxytocic drugs and evacuation of the uterus whilst anaemia and sepsis apparently reduced these women's chances of survival. Women who died (cases) from post abortion complications apparently received better reported quantitative care than controls. Recommendations based on this research report include improved education of health care workers and enhanced in-service training, regular audits of patients' records and changed policies for managing these conditions more effectively in Zimbabwe.